2011
DOI: 10.1088/0004-637x/730/1/5
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Feedback and the Epoch of Reionization: Clues in the Local Universe

Abstract: The source responsible for reionizing the universe at z > 6 remains uncertain. While an energetically adequate population of star-forming galaxies may be in place, it is unknown whether a large enough fraction of their ionizing radiation can escape into the intergalactic medium. Attempts to measure this escape fraction in intensely star-forming galaxies at lower redshifts have largely yielded upper limits. In this paper, we present new Hubble Space Telescope Cosmic Origins Spectrograph and archival Far-Ultravi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
405
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 288 publications
(439 citation statements)
references
References 84 publications
30
405
2
Order By: Relevance
“…Heckman et al 2011;Jones et al 2013). Saturated lines imply a high covering fraction of neutral gas along the line of sight.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Heckman et al 2011;Jones et al 2013). Saturated lines imply a high covering fraction of neutral gas along the line of sight.…”
Section: Discussionmentioning
confidence: 99%
“…Our sample was selected from Bergvall et al (2006), Heckman et al (2011), Leitet et al (2013). To this, we added Tol 1214−277 and GP1219+15, which show a Lyα profile that is highly suggestive of Lyman-continuum leakage according to our predictions in Sects.…”
Section: Comparison With Other Leaking Indicatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five local FUSE galaxies were observed in this pilot study, and they were all found to be essentially black in the C ii λ1036 Å line. Grimes et al (2009) and Heckman et al (2011) increased the sample size with a factor ≈3 using FUSE archival data. Neither found strong evidence of any large leakage, although three of the galaxies were found to have rather high upper limits, f esc < 10−18%.…”
Section: The C Ii λ1036 å Escape Fractionmentioning
confidence: 99%